The gamma spectrometry in the experimental teaching of Physics - Soto, R. L. (2014)
In this work, we made an analysis of the learning and teaching circumstances of the Physics School and in this context, we analyze an experiment that familiarizes the student with basic nuclear instrumentation which includes techniques and measurements methods of gamma rays spectrometry using radioactive sources of 22Na, 60Co, 137Cs and a NaI(Tl) scintillation detector. This experiment includes, also, the development of a multichannel analyzer prototype.